Life Unworthy of Living? A Short History of Euthanasia - Machinek, Marian (Studia Warmińskie, 2011)
A historical analysis of a certain idea is not only attempt to reconstruct past events as accurately as possible, but it also aims at better understanding of current intellectual trends. The idea of euthanasia is the best example here. Old justifications to allow to kill on request appear in today’s discussions almost literally. First of all it is compassion for the ill and suffering and necessity to alleviate their excruciating pain. This argument seems to be so clear and evident that the supporters of euthanasia quote it in the first place. Suggestive propaganda, particularly in films and documentaries, which show the demand for euthanasia as a sign of despair or even courage, is to break the instinctive resistance of the society. But when euthanasia is legalized (or acknowledged as not a punishable act), personal autonomy arguments are promoted. The pseudo-right to terminate one’s own life is popularized. This right encapsulates not only suicidal death by the ill person himself, but also patients’ demands for the possibility to be legally killed by doctors within the health care system. Stressing the issue of costs and eugenic aspects only reinforces the impression of a rational and human-friendly decision. The fact that this expanding pro-euthanasia mentality threatens the foundations of our civilization is marginalized and omitted. This mentality recognizes human life as valuable and worthy living only under certain conditions, namely when it has a good quality.